Karakteristik Tegangan Tembus Gas CO2 Dengan Menggunakan Pembangkit Tegangan Tinggi DC Polaritas Positif - Noviansyah Noviansyah; Fri Murdiya (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
The Sulfur hexafluoride (SF6) gas is the most widely used in high voltage applications, such as in gas insulated switchgear (GIS) and the gas circuit breaker (GCB) due to good insulation performance. However, SF6 gas has very serious problems for the environment, namely the global warming potential is very high. Of course, the study of alternative gas is required such as cabon dioxide (CO2), nitrogen (N2), and others for high voltage insulation. From the results of breakdown test on CO2 gas with the needles electrodes configuration or the spheres electrodes for several pressure gas level at 1 bar, 2 bars, 3 bars, and 4 bars, respectively, show the breakdown voltage of CO2 gas is proportional to pressure gas. Then, from the research data were also obtained that the breakdown voltage of CO2 gas is greater than the air. The analysis of weibull distribution weibull probability indicates that the voltage for the breakdown voltage of CO2 gas is proportional to the pressure of the gas. breakdown voltage also proportional to the distance between the needle-needle electrodes or sphere electrodes.Key words: CO2 gas, weibull distribution, breakdown voltage